1992
DOI: 10.1213/00000539-199208000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Low-Dose 3-in-1 Nerve Blockade for Postoperative Pain Relief After Total Knee Replacement

Abstract: We have investigated the value of a 3-in-1 nerve block, followed by a continuous low-dose infusion of bupivacaine into the femoral nerve sheath for postoperative analgesia after total knee replacement. Thirty-seven patients were randomly allocated to either a control group or a study group. The study group had a catheter placed in the ipsilateral femoral nerve sheath. A 3-in-1 nerve block was then performed in the study group with injection of 30 mL of 0.25% bupivacaine through the catheter. This was followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 0 publications
1
42
0
6
Order By: Relevance
“…[1][2][3][4][5][6][7] It may allow faster rehabilitation as measured by the maximal degree of knee flexion and walking distance obtained in the early postoperative days, length of hospitalization, and total length of rehabilitation. [1][2][3][4][5] Postoperative epidural analgesia is relatively contraindicated since these patients are usually anticoagulated for the prevention of deep venous thrombosis and pulmonary embolism.…”
Section: Conclusion : Comparativement à L'aac Les Deux Blocs Continumentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] It may allow faster rehabilitation as measured by the maximal degree of knee flexion and walking distance obtained in the early postoperative days, length of hospitalization, and total length of rehabilitation. [1][2][3][4][5] Postoperative epidural analgesia is relatively contraindicated since these patients are usually anticoagulated for the prevention of deep venous thrombosis and pulmonary embolism.…”
Section: Conclusion : Comparativement à L'aac Les Deux Blocs Continumentioning
confidence: 99%
“…8 Thus, many clinicians now rely on a continuous three-in-one femoral nerve (FEM) block to provide postoperative analgesia after TKR. [2][3][4]6 The femoral, or anterior, approach to the lumbar plexus is simple and has virtually no risk of major complications; however, postoperative pain scores from patients receiving continuous FEM blocks are higher than those measured in patients receiving continuous epidural analgesia, at least up to four hours after the surgery. 2 Inability of the femoral approach to block the sciatic nerve may explain its decreased efficacy compared to epidural analgesia; however, Allen et al found no benefit from the addition of a single injection sciatic nerve block to a FEM block in patients undergoing TKR.…”
Section: Conclusion : Comparativement à L'aac Les Deux Blocs Continumentioning
confidence: 99%
“…A systematic review of 112 studies between 1996 and 2005 by the PROSPECT working group supports the use of femoral nerve blocks for postoperative analgesia for primary TKA, based on the reduction in pain scores and supplemental analgesia (10). Of the 112 studies, 5 investigated the use of continuous infusion femoral nerve block versus placebo (8,(18)(19)(20)(21), all of which noted reduced pain scores at rest and with motion at 24 and 48 hours with CFNB.…”
Section: Discussionmentioning
confidence: 99%
“…The opioid sparing in the CPNB group lead to decreased incidence of nausea and other opioid-related side-effects. 3 Similarly, Edwards et al 12 showed that CPNBs could decrease opioid consumption on postoperative days 0, 1, and 2 compared to single shot PNBs in patients who underwent Total Knee Arthroplasty (TKA). Indeed, PNBs protect against opioidinduced cardiovascular, respiratory, and gastrointestinal side effects.…”
Section: Peripheral Nerve Blockade and Narcotic Consump-tionmentioning
confidence: 99%
“…Indeed, PNBs protect against opioidinduced cardiovascular, respiratory, and gastrointestinal side effects. 8,12,13 Although continuous PNBs have been shown to be more efficacious in treating postoperative pain 9,12-28 and decreasing opioid use, single injection PNBs have been demonstrated to provide superior pain control and decreased side-effects compared to opioid monotherapy. 8,13 Altering the concentration of the local anesthetic used in the block can also modify narcotic consumption.…”
Section: Peripheral Nerve Blockade and Narcotic Consump-tionmentioning
confidence: 99%